THE EFFECT OF TECHNOSTRESS ON ONLINE LEARNING BEHAVIOUR AMONG UNDERGRADUATES - Mohd Aidil Riduan Awang Kader; Nurul Nadia Abd Aziz; Suhanom Mohd Zaki; Maisarah Ishak; Siti Fahazarina Hazudin (Malaysian Journal of Learning and Instruction, 2022)
Purpose – Students’ incompetence to deal with the intricacies of technology during the teaching and learning process may have negatively affected their online learning process particularly throughout the COVID-19 pandemic. It is critical to research technostress influence on online learning behaviours among undergraduates. Thus, this research intends to examine the predicting factors that contribute to technostress and the correlation between undergraduates’ technostress and the behavioural intention to use online learning. Methodology – This study employed an online survey and cross-sectional data towards 212 respondents, all of whom were Diploma students from Universiti Teknologi MARA (UiTM) Pahang. This study added three new variables to the existing Unified Theory of Acceptance and Use of Technology (UTAUT) namely teaching-related aspects, price value, and technostress. Structural equation modelling (SEM) was performed to analyse the measurement model and evaluate the developed hypotheses. Findings – The findings established a significant correlation between technostress and behavioural intention to use online learning. Facilitating conditions also demonstrate a significant relationship to technostress. Significance - The study’s findings are likely to increase researchers’ understanding of the present condition of technostress in higher education as a consequence of the implementation of online learning regulations, as well as the scale of the impacts on higher education.